2023
DOI: 10.3390/ijms24065303
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Belantamab Mafodotin on Primary Myeloma–Stroma Co-Cultures: Asymmetrical Mitochondrial Transfer between Myeloma Cells and Autologous Bone Marrow Stromal Cells

Abstract: Belantamab mafodotin (belamaf) is an afucosylated monoclonal antibody conjugated to the microtubule disrupter monomethyl auristatin-F (MMAF) that targets B cell maturation antigen (BCMA) on the surface of malignant plasma cells. Belamaf can eliminate myeloma cells (MMs) through several mechanisms. On the one hand, in addition to inhibiting BCMA-receptor signaling and cell survival, intracellularly released MMAF disrupts tubulin polymerization and causes cell cycle arrest. On the other hand, belamaf induces eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A potential mechanism of belantamab mafodotin was recently reported by Matula et al, who assessed the effect of belantamab mafodotin on primary myeloma-stroma co-cultures [ 15 ]. It was noticed that the MM BCMA expression level positivity varies between 31% and 96% among patients, and inadequate expression is associated with extremely high resistance to belantamab mafodotin.…”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism of belantamab mafodotin was recently reported by Matula et al, who assessed the effect of belantamab mafodotin on primary myeloma-stroma co-cultures [ 15 ]. It was noticed that the MM BCMA expression level positivity varies between 31% and 96% among patients, and inadequate expression is associated with extremely high resistance to belantamab mafodotin.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of functional mitochondria from MM-MSCs occurs through several mechanisms, including tunneling nanotubes, CD38 [177], and EVs, as well as cell-to-cell contact and the CXCL12/CXCR4 axis [55]. This mitochondrial trafficking supports the oxidative metabolism of tumor PCs, favoring cancer growth and drug resistance [55,[178][179][180][181].…”
Section: Role Of Mscs In In Multiple Myelomamentioning
confidence: 99%
“…This suggests that multiple myeloma cells resist chemical drugs by plundering mitochondria from stromal cells [72,73]. It has also been shown that multiple myeloma cells can resist belamaf (a monoclonal antibody conjugated with microtubule-disrupting agent monomethyl auristatin-F (MMAF)) through this mechanism, thus avoiding apoptosis [74]. In ALL, mitochondrial transfer occurs more frequently, and traditional chemotherapy drugs like AraC and DNR always fail to completely eliminate tumor cells [75].…”
Section: Mitochondrial Transfer Promotes Tumor Resistance To Chemothe...mentioning
confidence: 99%